PENERAPAN DISIPLIN POSITIF DALAM PEMBELAJARAN DITINJAU MELALUI PERSPEKTIF KRISTEN [POSITIVE DISCIPLINE IN LEARNING REVIEWED THROUGH A CHRISTIAN PERSPECTIVE] - Aji, Imanuela Praba; Tamba, Kimura Patar (Universitas Pelita Harapan, 2020)
Discipline is still a problem in the world of education. In addition, disciplinary enforcement still uses punishment. This deviant behavior of students is a result of humanity's fall into sin. Sin turns people away from God and they choose to become God's rebels. Therefore, humans become more likely to disobey. Having good discipline is the expectation that every teacher wants for their students. However, the teacher prefers to make his students obedient to him but it is not always accompanied by a growing awareness to be disciplined in the hearts of students. One form of application that encourages discipline with compliance is positive discipline. The author wants to analyze the application of positive discipline through a Christian perspective. Positive discipline is a disciplined approach based on trust between teachers and students. The analysis shows that the application of positive discipline in accordance with Christian principles has not been able to stop indiscipline. This is evident from the responses of students who are still repeating their actions even though positive discipline has been applied in learning. One of the forms of applying positive discipline that is in line with Christianity's view is one of the results of awareness and changes in student attitudes not because of dialogue but because of the touch of the Holy Spirit. In its application, it must always rely on the intervention of the Holy Spirit.BAHASA INDONESIA ABSTRACT: Ketidakdisiplinan masih menjadi permasalahan di dalam dunia pendidikan. Selain itu penegakkan kedisiplinan masih menggunakan hukuman. Perilaku menyimpang siswa ini merupakan akibat dari kejatuhan manusia ke dalam dosa. Dosa membuat manusia menjadi berpaling dan memilih untuk menjadi pemberontak Allah. Oleh sebab itu, manusia menjadi lebih menyukai melakukan ketidaktaatan. Memiliki kedisiplinan yang baik merupakan harapan yang setiap guru inginkan terhadap siswanya. Akan tetapi, guru lebih suka membuat siswanya patuh kepadanya tetapi tidak diiringi dengan menumbuhkan kesadaran untuk berdisiplin dalam hati siswa. Salah satu bentuk penerapan yang mendorong kedisiplinan dengan kepatuhan adalah disiplin positif. Tujuan penelitian ini adalah menganalisis penerapan disiplin positif melalui perspektif Kristen. Disiplin positif merupakan sebuah pendekatan disiplin yang berdasarkan kepada rasa kepercayaan antara guru dan siswa. Hasil analisis menunjukkan penerapan disiplin positif sudah sesuai dengan prinsip kekristenan namun belum dapat menghentikan ketidakdisiplinan. Hal ini terbukti dari respon siswa yang masih mengulangi perbuatannya meskipun telah diterapkan disiplin positif di dalam pembelajaran. Bentuk penerapan disiplin positif yang sesuai dengan pandangan Kekristenan salah satunya adalah hasil dari kesadaran dan perubahan sikap siswa bukan karena adanya dialog tetapi karena jamahan Roh Kudus. Seharusnya dalam penerapannya harus selalu mengandalkan campur tangan Roh Kudus.